2013
DOI: 10.1371/journal.pone.0078657
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Pattern of Dry Eye after Cataract Surgery

Abstract: PurposeTo evaluate the incidence and severity pattern of dry eye after phacoemulsification.SettingKing Chulalongkorn Memorial Hospital, Bangkok, Thailand.DesignProspective descriptive study.MethodsSamples were collected from ninety-two uncomplicated cataract patients who were 18 years old or older. Dry eye incidence and pattern were analyzed at days 0, 7, 30 and 90 after phacoemulsification using (1) Ocular Surface Disease Index (OSDI) questionnaire, (2) tear break up time (TBUT), (3) Oxford ocular surface sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
164
1
40

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(221 citation statements)
references
References 28 publications
16
164
1
40
Order By: Relevance
“…Cataract surgery can improve the visual acuity largely. However, a significant number of patients complain of postoperative dry eye symptoms such as dry, foreign body sensation and shorttime but frequent blurred vision [1][2][3][4][5]. From our experience, the patients may blame the surgery (and their surgeon) for the apparently new development of dry eye symptoms and generally do not realize that their problem stems from ocular surface disease rather than the surgical procedure.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Cataract surgery can improve the visual acuity largely. However, a significant number of patients complain of postoperative dry eye symptoms such as dry, foreign body sensation and shorttime but frequent blurred vision [1][2][3][4][5]. From our experience, the patients may blame the surgery (and their surgeon) for the apparently new development of dry eye symptoms and generally do not realize that their problem stems from ocular surface disease rather than the surgical procedure.…”
Section: Introductionmentioning
confidence: 88%
“…To avoid these accusations and to inform patients preoperatively of the possibility of dry eye symptoms following surgery, it is equally important to provide information about when these symptoms will diminish or disappear. The severity of dry eye symptoms has been reported to peak 7 days after cataract surgery and to persist for 3 months, and it can become both physically and psychologically debilitating [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] One important differentiating feature was that in this study most cases underwent phacoemulsification and only a few cases were of SICS and ECCE. We have also compared the dry eye incidence between phacoemulsification and SICS.…”
Section: Discussionmentioning
confidence: 99%
“…Kasetsuwan Ngamjit, et al showed that the incidence of dry eye in patients who all underwent phacoemusification was 9.8%. 11 Kavitha et al found that after manual small incision cataract surgeries with corneoscleral tunnel incisions, 66.2% of the patients had dry eyes, which was relatively high. 12 The 22.1 % incidence in our study is in between the above quoted studies as our sample consisted of both SICS, phacoemulsification and conventional ECCE of which phacoemulsification constituted the majority.…”
Section: Discussionmentioning
confidence: 99%